Analisis Kesehatan Bank Dengan Metode RGEC Pada Bank Yang Terdfatar Di Bursa Efek Indonesia Periode 2019-2021 - Moch. Rafli Sadam; Pratama Indra Sutrisno (Universitas 45 Surabaya, 2023)
Bank health is the bank's ability to regularly carry out banking activities and fulfill its responsibilities in accordance with Bank Indonesia Regulation No. 13/1/PBI/2011. To assess the health of the bank using the Risk profile, Good Corporate Governance, Earnings, and Capital (RGEC) method which uses measurements of non-performing loans (NPL), loan to deposit ratio (LDR), Good Corporate Governance (GCG), return on assets (ROA), return on equity (ROE), operating expenses to operating income, and capital adequacy ratio (CAR). This research uses a quantitative descriptive approach, this study uses a causal design or causal relationship. To determine the soundness level of a bank, there is a matrix of determining criteria for each variable. The criteria for this determination are based on Bank Indonesia Circular No. 13/24/DPNP of 2011. The data source for this study uses conventional banking secondary data at banks listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample was determined as many as 78 observations. From the results of the research that has been done, it can be concluded that there are banks that have conditions of